CYANIDE DETECTION ABILITY OF THE PbO2 ELECTRODE SYNTHESIZED BY PULSED CURRENT METHOD - Binh, Phan Thi; Thanh Thuy, Mai Thi; Toan, Nguyen Van; Doan, Duong Thi (Vietnam Journal of Chemistry, 2012)
Lead dioxide electrode was prepared by pulsed current method on stainless steel (pulse height: 30 mA/cm2, pulse width: 1 s, Q = 5100 mAs) from solution of 0.5 M HNO3 + 0.5 M Pb(NO3)2 + 0.05 M Cu(NO3)2 at room temperature. The electro-catalytic oxidation of cyanide on PbO2 was investigated by potentiodynamic method at different scan rates in medium of 0.1 M NaOH. The result showed that PbO2 can electrocatalyse oxidation process of CN- which occurred at about 0.6 V versus to saturated calomel electrode. It was found a linear relationship between the height of oxidation peak and cyanide concentration, which is better than that between oxidation peak area and cyanide concentration. The both lines have R2 equal 0.9989 and 0.9934, respectively. The electro-catalytic activity of PbO2 layer is depended exponentially on their thickness. Keyword: PbO2, cyanide, electro-catalysis.